INKLUSI PADA SURAT KABAR ONLINE: ANALISIS WACANA KRITIS BERDASARKAN SUDUT PANDANG THEO VAN LEEUWEN - Winda - Azmi (Universitas Negeri Padang, 2021)
This study aims to determine the contents of the theory of Leeuwen on online news coming from 5 sources, namely JavaPos.com, Okezone News, Rakyatku.com, Wahanariau.com, and Sindo News. The data in this study are phrases, clauses, and sentences related to inclusion in Leeuwen's theory with the theme of rape on online news. The source of this research data obtained from online news as much as 5 news. The data were analyzed by (1) identifying data according to Leeuwen's inclusion theory, (2) classifying the data based on the theory to be referenced, (3) analyzing the data by recording the phrase, the sense or phrases associated with Leeuwen inclusion theory, (4) interpreting data that has been analyzed with Leeuwen's inclusion theory, and (5) describing the description data by writing the report. The results of this study suggest that there is Leeuwen's inclusion theory on five online news with the theme of rape in the online news with the theme of rape as a whole the author does not side with the actor or writer and is also not aligned to the victim. Of the 5 online news analyzed, there is three news titled “Rape Teacher and Kill the Health Waiter, OPM Can not Sympathize the World